Neocolonial Thinking and Respect for Nature: Do Indigenous People have Different Relationships with Wildlife than Europeans? - Pierotti, Raymond; Fogg, Brandy Raelene (Ethnobiology Letters, 2020)
We respond to Mech (2019) “Do Indigenous American Peoples’ Stories Inform the Study of Dog Domestication” and point out a number of errors and omissions in Mech’s essay. These include: 1) assuming that the behavior of all wild wolves is the same, and can be characterized according only to Mech’s personal experience; 2) assuming that the domestication of wolves took place in only a single location at one time (14,000 yrs BP); 3) misrepresenting the statements and findings of other scholars; 4) assuming that all wolves that have ever encountered humans have experienced persecution; and 5) dismissing all accounts of interactions with wolves by Indigenous Americans. The last of these is particularly egregious and seems to represent a form of neocolonial thinking, in which only accounts and findings by Europeans are considered to be acceptable evidence. Mech’s own work on Ellesmere Island seems to support the idea that wolves can be curious and unthreatening to humans. We suggest that this might be the only actual time Mech interacted with true Canis lupus. In addition, Mech’s statements on wolf attacks and the significance of rabies are shown to be misleading. As a result, Mech’s work, especially his questioning of the validity of Indigenous knowledge, which often provides crucial insights into some aspects of ethnobiological research, represents a critique of methods employed by scholars within the discipline of ethnobiology, whereas, as a wildlife biologist, Mech seems to lack knowledge of the principles of ethnobiology.